If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(10-x)2/7-1=-5
We move all terms to the left:
(10-x)2/7-1-(-5)=0
We add all the numbers together, and all the variables
(-1x+10)2/7-1-(-5)=0
We add all the numbers together, and all the variables
(-1x+10)2/7+4=0
We multiply all the terms by the denominator
(-1x+10)2+4*7=0
We add all the numbers together, and all the variables
(-1x+10)2+28=0
We multiply parentheses
-2x+20+28=0
We add all the numbers together, and all the variables
-2x+48=0
We move all terms containing x to the left, all other terms to the right
-2x=-48
x=-48/-2
x=+24
| 3/4x+2/5=3 | | 4/7=2/x | | 7-5x=93 | | a^2+a^2=40^2 | | X/2+12=2x-2 | | 2/3+x-1+3/5=0 | | 5x2+15x-20=0 | | 1+6n=8n+15 | | 9y-11=(y+2) | | 6x+14=6+5x | | 2x-8=12=15 | | 1/2(x^2+4)=6 | | -2n/5=7 | | 1-8n=1-4n | | 2x-8=+2 | | 5x^2+10x=73 | | 0.4(x+12)=0.6+3.2 | | 2+6x=5x-5 | | Y=4x(x-5) | | 2y-8y+3y-y-1+5-13=0 | | 4n-3=5n+3 | | -2x+(2x+8)^2=-8 | | 6-x=6x+34 | | 5-2x=1-3x | | 4x+2x+x-15=0 | | 13+10y=-14 | | -2+n=3-4n | | 12(2x−6)+5=23x+9+73x | | 6x-11=5x-7 | | -13.9=-1.1+x/8 | | 12n-9n-6+10=0 | | (2x+6)^2=2x-6 |